2020
DOI: 10.1186/s12955-020-01354-8
|View full text |Cite
|
Sign up to set email alerts
|

Equity, acceptability and feasibility of using polyunsaturated fatty acids in children and adolescents with autism spectrum disorder: a rapid systematic review

Abstract: Introduction: Some recent randomized controlled trials (RCTs) assessed the efficacy and safety of polyunsaturated fatty acids (PUFAs) for the treatment of autism spectrum disorder (ASD). To optimally inform the Italian guideline for the management of ASD in children and adolescents, we reviewed the impact on equity, acceptability and feasibility for developing a pilot recommendation for PUFAs. Methods: We performed a rapid systematic review of observational and experimental studies on PUFAs for children and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
3
5
0
Order By: Relevance
“…Finally, the use of the EtD framework requires the panel to be familiar with the tool [124]. To overcome this potential limitation, about 2 months before the presentation of the body of evidence on antipsychotics, an EtD framework on a pilot question was presented to the panel [125,126] for the formulation of a recommendation on the use of polyunsaturated fatty acids. This recommendation will not take part to the Italian guidelines on the diagnosis and treatment of children and adolescents with ASD.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Finally, the use of the EtD framework requires the panel to be familiar with the tool [124]. To overcome this potential limitation, about 2 months before the presentation of the body of evidence on antipsychotics, an EtD framework on a pilot question was presented to the panel [125,126] for the formulation of a recommendation on the use of polyunsaturated fatty acids. This recommendation will not take part to the Italian guidelines on the diagnosis and treatment of children and adolescents with ASD.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Although the efficacy of PUFAs in children and adolescents with ASD is still controversial, PUFAs are administered to a portion of this population ranging from 18 to 51% [67,68], probably thanks to the fact that costs and difficulties of implementation appear negligible [69], and safety concerns seem small [65]. Also the rationale behind the administration of PUFAs in individuals with ASD, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the EtD framework in general, and the evaluation of its domains relating to equity, acceptability and feasibility, requires the panel to be familiar with the tool [ 63 ], and this is a potential limitation for the process of developing recommendations. To overcome this potential limitation, about 2 months before the presentation of the body of evidence on antipsychotics, an EtD framework on a pilot question was presented to the panel [ 64 , 65 ]. In other experiences, panel members have reported that, when familiarity with the EtD framework is achieved, the tool helped them in structuring discussion, saving time, ensuring systematicity in the process of recommendation formulation [ 66 ].…”
Section: Discussionmentioning
confidence: 99%